E-Learning, Time and Unconscious Thinking. (April 2014) - Mathew, David
This article views the temporal dimensions of e-learning through a psychoanalytic lens, and asks the reader to consider links between online learning and psychoanalysis. It argues that time and its associated philosophical puzzles impinge on both psychoanalytic theory and on e-learning at two specific points. The first is in the distinction between unconscious mental activity and conscious thinking. In psychoanalysis we would talk of the distinction between primary and secondary processes, and here the article notes the learner's disregarding of the category of time in the former, and the learner's cognizance of it in the latter, exploring some of the characteristics of both of these processes. The learner's sense of time is a result of experiencing delay between desire and satisfaction. Here, the wish-fulfilling propensities of the primary processes deny time, whereas the adaptive propensities of the secondary processes lead to its discovery. The second specific point of interest is a viewing of Freud's theory of memory from a contemporary pedagogic standpoint. Freud's theory of memory assumes that all past experiences are represented in the present and are capable of manifesting an effect on the present. The article asks the reader to consider how this might challenge the learner.